1986
DOI: 10.1557/proc-84-771
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric Dating of Ochoan (Permian) Evaporites, Wipp Site, Delaware Basin, New Mexico, Usa

Abstract: We have attempted radiometric dating of halide-sulfate salts and clay minerals from the Delaware Basin, New Mexico, USA, as part of geochemical study of the stability of the evaporite sequence at the WIPP (Waste Isolation Pilot Plant--a US DOE facility) site. We undertook this dating to determine: (1) primary age of evaporite genesis or time(s) of recrystallization, (2) if previously undated evaporite minerals (leonite, polyhalite, kieserite) give useful data, and (3) if the detrital clay minerals have been ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1996
1996
1996
1996

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, Obradovich et al (1982) have indicated that their and other work predicted K-Ar ages of 245 Myr for polyhalite and langbenite, generally agreeing with Brookins and Lambert (1987) and non-isotopic geological age dating estimates of 240 Myrs. For example, Obradovich et al (1982) have indicated that their and other work predicted K-Ar ages of 245 Myr for polyhalite and langbenite, generally agreeing with Brookins and Lambert (1987) and non-isotopic geological age dating estimates of 240 Myrs.…”
Section: Age Datingmentioning
confidence: 65%
See 2 more Smart Citations
“…For example, Obradovich et al (1982) have indicated that their and other work predicted K-Ar ages of 245 Myr for polyhalite and langbenite, generally agreeing with Brookins and Lambert (1987) and non-isotopic geological age dating estimates of 240 Myrs. For example, Obradovich et al (1982) have indicated that their and other work predicted K-Ar ages of 245 Myr for polyhalite and langbenite, generally agreeing with Brookins and Lambert (1987) and non-isotopic geological age dating estimates of 240 Myrs.…”
Section: Age Datingmentioning
confidence: 65%
“…Brookins and Register (1981) and Brookins and Lambert (1987) report that both argon and Rb-Sr isotope determinations show that the deposit is 210 ± 10 million years old. Brookins and Register (1981) and Brookins and Lambert (1987) report that both argon and Rb-Sr isotope determinations show that the deposit is 210 ± 10 million years old.…”
Section: Age Datingmentioning
confidence: 99%
See 1 more Smart Citation